ANALISA PENJADWALAN PROYEK DENGAN METODE PERT DAN CPM PADA PEMBANGUNAN GEDUNG HOTEL DI SIDOARJO - Moch Syamsul Maarif (AGREGAT, 2022)
The probability of the project being completed on time or according to plan with PERT and CPM methods with Microsoft Project Application is 66%. From the distribution of questionnaires to 26 respondents, it can be concluded that the 3 main factors causing delays in the hotel building project in Sidoarjo, project delays are due to technical factors with a preset value of 87.85%, project delays due to financial factors with a preset value of 77.31%, project delays due to labor and equipment factors with a preset value of 71.03%.